Pragmatic Analysis of Politeness Strategies in the Spilled Milk Podcast Episode: 'An Unfiltered Conversation with My 3-Year-Old Son - Ester Sitorus; Selviana Napitupulu (Jurnal Ilmu Sosial dan Humaniora, 2026)
This research analyzes how parents use politeness strategies when communicating with their children during spontaneous conversations. It aims to determine the variety of strategies exhibited and their practical purpose in the communication process between parents and children. This qualitative analysis of the conversation uses a descriptive design; data were collected by carefully listening to and writing down the audio recordings from an identified parenting podcast episode where a parent interacts with their toddler during a spontaneous conversation. Data collected were analyzed using Brown and Levinson’s (1987) politeness theory to categorize identified strategies and how each was used for a particular interactional purpose. In summary, four categories of Politeness Strategies were discovered in the data analysis based on their contextualized practical uses: 1) Bald on Record,2) Positive,3) Negative and 4) Off Record. Bald on Record Strategies were found to be the most commonly used strategy for the purpose of clarity and directness in parent-child interaction. Positive politeness techniques were utilized to foster solidarity and encouragement, while negative politeness approaches allowed for decreased imposition and respect the autonomy of the child. Off-record techniques were predominantly employed to display playfulness and creativity. Overall, this research illustrates that both positive and negative politeness techniques act not only as a means of interaction but also represent a source of pragmatic resource for directing behaviour, sustaining interpersonal harmony, and aiding in the child’s social and linguistic growth within informal familial settings.